Ventilation control using dedicated outdoor air system (DOAS) - Muhammad Faris, Ahmad (2014)
There are various forms of Heating, Ventilation and Air Conditioning (HVAC) systems available in the market today. Active Chilled Beams (ACB) have grown to be the center of attention and favored by consumers when considering implementing a HVAC system. Its reputation and demand is thriving due to its many inherent benefits. ACB benefits includes energy efficiency, reduced building height and space requirement. This project will examine the control of the ACB. Different control schemes will be analyzed to compare and contrast. Upon studying the different control schemes employed on the ACB, the best control can be chosen. Criteria to be met will be simplicity, robustness, controllable and minimal error. Comprehensive data documentation under various condition will be practiced so as to have a better understanding of this practical system.